Receptions of Human Dimension in the Context of Anthropological Discourse of Humanistic Management - Valentina Voronkova (International Society of Philosophy and Cosmology, 2016)
The subject of research is the perception of human dimension as the anthropological aspect of humanistic management, based on the interrelations between man, government, society. The paper describes the evolution of views on man in the context of anthropological foundations of humanistic management;it is noted that the development trends of the philosophical and anthropological knowledge of humanistic management are based on human perception in the projection of anthropological dimensions of man, which is fundamental in European philosophy. The paper analyzes the essence of human dimension as anthropological paradigm of humanistic management, in which man is not only economic, or political, but also the spiritual and cultural member of society; gives the analysis of human dimension as anthropological paradigm of European philosophy that investigates the anthropological foundations of economic, political and social spheres, interprets conditions of creating a humane society, in which the imperatives of a just society should be implemented. Characteristics and features, as well as the conditions for achieving human dimension as the anthropological foundation of European humanistic management are disclosed. The acquired knowledge can be useful for solving anthropological problems of humanistic management.